Structural and functional complexity of the humoral response against the Trypanosoma cruzi ribosomal P2β protein in patients with chronic Chagas' heart disease - Mahler, Ebelina Barbara (2004)
High levels of antibodies against the C-terminus of the Trypanosoma cruzi TcP2β ribosomal protein, defined by the peptide EEEDDDMGFGLFD, named R13, have been measured in sera from patients with chronic Chagas' Heart Disease (cChHD). These antibodies also recognize an epitope on the second extracellular loop of the β1-adrenergic receptor, inducing a functional response on cardiomyocytes. The aim of this study was to gain novel insights into the structural basis of this cross-reactivity as well as to evaluate the origin of anti-M2- cholinergic receptor antibodies, which are also commonly found in cChHD patients. To address these questions we immunopurified anti-R13 antibodies and studied the structural requirements of epitope recognition. Results showed that the immunopurified antibodies recognized a conformation of R13 in which the third Glu residue was essential for binding, explaining their low affinity for the mammalian homologue (peptide H13: EESDDDMGFGLFD). Alanine mutation scanning showed individual variations in epitope recognition in each of the studied patients. The importance of a negatively charged residue at position 3 for the recognition of anti-R13 antibodies was further confirmed by competition experiments using a Ser3-phosphorylated H13 analogue, which had 10 times more affinity for the anti-R13 antibody than the native H13 peptide. Moreover, anti-R13 antibodies stimulated either the β1-adrenergic or the M2-cholinergic receptor, in strict agreement with the functional properties of the IgG fractions from which they derived, demonstrating that the same parasite antigen may generate antibody specificities with different functional properties. This may be a clue to explain the high variability of electrophysiological disturbances found in cChHD.